Evaluating Public Space - Mehta, Vikas (Journal of urban design, 2014)
Public space plays an important role in sustaining the public realm. There is a renewed interest in public space with a growing belief that while modern societies no longer depend on the town square or the piazza for basic needs, good public space is required for the social and psychological health of modern communities. New public spaces are emerging around the world and old public space typologies are being retrofitted to contemporary needs. Good public space is responsive, democratic and meaningful. However, few comprehensive instruments exist to measure the quality of public space. Based on an extensive review of literature and empirical work, this paper creates a public space index to assess the quality of public space by empirically evaluating its inclusiveness, meaningfulness, safety, comfort and pleasurability. Four public spaces in downtown Tampa, Florida, are examined using the index and several applications for public space planners, designers and managers are suggested.